Mobility, sexual networks and exchange among bodabodamen in southwest Uganda - Nyanzi, Stella; Nyanzi, Barbara; Kalina, Bessie; Pool, Robert (An International Journal for Research, Intervention and Care, 2004)
In order to examine the sexual behaviour of a highly mobile social group, qualitative data and quantitative data were elicited from 212 private motorbike taxi-men, locally called bodabodamen, from two study sites in Masaka, Uganda. Selection criteria were availability and willingness to participate in the study. Research techniques employed were a questionnaire, focus group discussions, in-depth interviews and case studies. Findings indicate that bodabodamen are a highly mobile group who engage in frequent seasonal rural-urban migration. Consequent to this, bodabodamen have a wide network of both occasional and regular sexual partnerships. Both serial and concurrent multiple partnerships are with adults, youths, widows, students, sugar-mummies, barmaids, commercial sex workers, tailors. Exchange plays a significant role in sexual negotiations but the act of giving to a sexual partner is ambivalent in its social interpretation. Since bodabodamen have regular access to cash, they have higher bargaining power for sex. Implications for HIV/ AIDS prevention are discussed.
Keywords: Mobility; sexual networks; bodabodamen; southwest Uganda